Principles of Educating Preschool Children in the National Spirit - Dildora Abdullajonova (International Journal on Integrated Education, 2022)
The article discusses the specifics and principles of educating preschoolers in the national spirit. The essence of these principles is explained in terms of their importance in the practice of the field.